2008
DOI: 10.1016/j.jplph.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial alternative pathway is associated with development of freezing tolerance in common wheat

Abstract: Cold acclimation is an adaptive process for acquiring cold/freezing tolerance in wheat. To clarify the cultivar difference of freezing tolerance, we compared mitochondrial respiration activity and the expression profile of alternative oxidase (AOX) genes under low-temperature conditions using two common wheat cultivars differing in freezing tolerance. During cold acclimation, the respiration capacity of the alternative pathway significantly increased in a freezing-tolerant cultivar compared with a freezing-sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…There is evidence that AOX activity is strongly enhanced by stress (Finnegan, Soole & Umbach 2004), including water stress (Bartoli et al 2005;Ribas-Carbo et al 2005), low temperatures (Matos et al 2007;Mizuno et al 2007) and excess light (Noguchi et al 2005;Yoshida, Terashima & Noguchi 2007), and that it serves as a supplementary electron sink, probably to regenerate NAD + and/or to prevent generation of reactive oxygen species (Amirsadeghi et al 2006). A core hypothesis of our model is that po is downregulated to maintain flux balance, first by reducing TCA cycle activity, and then by downregulation of po.…”
Section: Flux Balance Constraints On P : O Ratio and Photoreductant Ementioning
confidence: 96%
“…There is evidence that AOX activity is strongly enhanced by stress (Finnegan, Soole & Umbach 2004), including water stress (Bartoli et al 2005;Ribas-Carbo et al 2005), low temperatures (Matos et al 2007;Mizuno et al 2007) and excess light (Noguchi et al 2005;Yoshida, Terashima & Noguchi 2007), and that it serves as a supplementary electron sink, probably to regenerate NAD + and/or to prevent generation of reactive oxygen species (Amirsadeghi et al 2006). A core hypothesis of our model is that po is downregulated to maintain flux balance, first by reducing TCA cycle activity, and then by downregulation of po.…”
Section: Flux Balance Constraints On P : O Ratio and Photoreductant Ementioning
confidence: 96%
“…Much works have shown that the AOX pathway, AOX transcript abundance, and AOX protein amount are increased under various stressful conditions, including chilling (Mizuno et al 2008), drought (Ribas-Carbo et al 2005;Bartoli et al 2005), phosphate limitation (González-Meler et al 2001), and plant diseases (Simons et al 1999). Recent work reported that treatment of Citrus cell suspensions with high concentration of NaCl led to a stimulation of the capacity of the AOX pathway and an increase in AOX protein amount (Ferreira et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A temporal difference exists between developmental-and cold-induced increases, in that the accumulation of intron-containing transcripts is maximized half to one day after imbibition, whereas 3 to 7 days are required after cold treatment. However, mitochondrial responses are shared by germinating seeds and cold-treated plants, such as increased O 2 uptake capacity, differential fluxes between cyanide-sensitive (mainly, cytochrome) and -insensitive respiratory (AOX) pathways, and the activation of some mitochondrial genes encoded in the nuclear genome 3,42,52,62 . It is possible that one or more of these responses is directly associated with the accumulation of intron-containing transcripts and will shed light on the physiological significance of the phenomenon.…”
Section: Mitochondria-encoded Gene Expressions In Wheat (Triticum Aesmentioning
confidence: 99%